Typographic design in the digital studio : application skills modules - Amdur, David A. (Thomson, 2007)
The craft of graphic design requires mastery of typographic design and of the digital applications used to execute it--these companion guides build capacities in both of these areas together. The Design Concepts book will guide readers to observe and reflect on how type functions and to develop strategies for creative typographic expression. The Application Skills Modules book pairs each lesson in typography with a lesson in the digital tools of design production. This book introduces the essential features of the Macintosh Operating System X (OSX) as well as Mac or PC versions of InDesign, Photoshop, Illustrator, and QuarkXPress, so readers can develop good working knowledge in one or all of these applications. A DVD in the Application Skills Modules book includes Quicktime movies demonstrating software lessons, exercise resources, and type specimens.